DIFFERENCES IN THE SPATIAL DISTRIBUTION AND CHARACTERISTICS OF URBAN BEGGARS: THE CASE OF THE SANGLAH DISTRICT IN DENPASAR (INDONESIA) - Shara, Aprilia Riszi Indah Dewi; Listyaningsih, Umi; Giyarsih, Sri Rum (Quaestiones Geographicae, 2020)
The study set out to analyse the differences in the characteristics and spatial distribution of urban beggars in Sanglah, Denpasar City. It employed survey research for data collection by observation, structured interviews with a questionnaire, and documentation. These data were later processed and analysed in a quantitative descriptive manner. The results show that, based on religion, there were two groups of beggars, namely Muslim and Hindu. Spatially, the Hindu beggars disregarded the religion of the people they implored, whereas the Muslim beggars would only target the houses and shops owned by Muslims. Those two class of beggars differ in languages, bagging duration, daily-earning, clothing, and sympathy-drawing strategy during the panhandling